If you build it, will they notice? public charging density, charging infrastructure awareness, and consideration to purchase an electric vehicle - Kelly Hoogland; Kenneth S. Kurani; Scott Hardman; Debapriya Chakraborty (Transportation Research Interdisciplinary Perspectives, 2024)
This research tests an implicit assumption about plug-in electric vehicle (PEV) charging infrastructure: people—including people not interested in PEVs—see public PEV charging. Data from a survey of all car-owning households in California are combined with data on public PEV charging and PEV registrations to estimate a structural equation model to test the direct and indirect effects of public charging density on whether participants see charging infrastructure and whether they have considered acquiring a PEV. We also explore the direct and indirect effects of seeing public charging on PEV purchase consideration. Results show the density of public charging is neither directly nor indirectly related to whether people see public charging or their level of PEV purchase consideration. Our results suggests that for public charging to drive PEV sales growth, it may need to be accompanied by strategies to increase consumers’ engagement with PEVs.